REVIEWING THE LEGAL CERTAINTY OF THE NATIONAL EXAMINATION - Dadang Gandhi (Jurnal Hukum Replik, 2021)
Whereas Article 31 Paragraph (2) of the 1945 Constitution (before the amendment) is the legal basis for the formation of Law Number 2 of 1989 concerning the National Education System (Law on National Education System), furthermore based on the provisions of Article 31 Paragraph (2) of the Law. The 1945 Constitution of the Republic of Indonesia (UUDNRI 1945) resulted from the amendment that has formed Law Number 20 of 2003 concerning the National Education System (New National Education System) as a substitute for the National Education System Law. According to Article 58 paragraph (1) and paragraph (2) of the new National Education System, provisions related to "evaluation of student learning are carried out by educators (teachers), while student evaluation is carried out by independent institutions. In this case, it is carried out by the National Education Standards Agency (BSNP).Furthermore, as the implementation of the new National Education System, Government Regulation Number 19 of 2005 in conjunction with Government Regulation Number 32 of 2013 in conjunction with Government Regulation Number 13 of 2013 concerning National Education Standards, which in Article 66 paragraph (1) regulates the National Examination (UN ) organized by the government, in this case, the BSNP.  Whereas according to the provisions of Article 58 paragraph (1) and paragraph (2) of the new National Education System, the evaluation of student learning outcomes and student evaluation is not the government's authority, in this case, BSNP. And BSNP was formed based on the Regulation of the Minister of Education and Culture Number 97 of 2013 concerning the National Education Standards Agency. Along with the development of the Covid 19 outbreak, the Minister of Education and Culture issued Circular Number 1 of 2021 regarding the Abolition of the National Examination in the Covid 18 situation, but along with the issuance of this circular the position of Article 66 paragraph (1) Government Regulation Number 13 of 2013 concerning The National Education Standards which are the basis for the implementation of the national examinations are still in effect, besides that the position of circulars in the statutory system is not included in one of the hierarchies of statutory regulations so that the elimination of the national exams itself creates legal uncertainty.Keywords: binoculars, certainty, law, negation, national examination.